Microstructure formation during thermomechanical processing in Ti-17 alloy - Chandiran Elango; Miyamoto Goro; Furuhara Tadashi (MATEC Web of Conferences, 2020)
The microstructure evolution during solution treatment at (alpha+beta) two phase region and subsequent aging process at 620 ˚C, after compressing the specimen in beta structure to different strain (0-70%) followed by cooling to room temperature has been investigated. Deformation strain hardly affects the total volume fraction of alpha phase after the solution treatment and aging process. On the other hand, with an increase in deformation strain, the volume fraction of the primary alpha phase increased although secondary alpha phase decreased, during the aging process, scuhdecrease in secondary alpha phase volume fraction results in a decrease in the strength. The loss of coherency of alpha/beta interphase boundaries at higher deformation strain promoted by dynamic recovery increases the interfacial mobility; which results in faster growth of primary alpha, thereby decreases secondary alpha precipitation.